A Rare Case of Vancomycin-Induced Linear Immunoglobulin A Bullous Dermatosis - Pinky Jha; Kurtis Swanson; Jeremiah Stromich; Basia M. Michalski; Edit Olasz (Case Reports in Dermatological Medicine)
Linear IgA bullous dermatosis (LABD) is an autoimmune vesiculobullous disease, which is typically idiopathic but can also rarely be caused by medications or infections. Vancomycin is the most common drug associated with LABD. Lesions typically appear 24 hours to 15 days after the first dose of vancomycin. It is best characterized pathologically by subepidermal bulla (blister) formation with linear IgA deposition at the dermoepidermal junction. Here we report an 86-year-old male with a history of left knee osteoarthritis who underwent a left knee arthroplasty and subsequently developed a prosthetic joint infection. This infection was treated with intravenous vancomycin as well as placement of a vancomycin impregnated joint spacer. Five days following initiation of antibiotic therapy, he presented with a vesiculobullous eruption on an erythematous base over his trunk, extremities, and oral mucosa. The eruption resolved completely when intravenous vancomycin was discontinued and colchicine treatment was begun. Curiously, complete resolution occurred despite the presence of the vancomycin containing joint spacer. The diagnosis of vancomycin-induced linear IgA bullous dermatosis was made based on characteristic clinical and histopathologic presentations.